2002
DOI: 10.1046/j.1440-1665.2002.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ECT in Schizophrenia

Abstract: Objective:To review the place of electroconvulsive therapy (ECT) in the treatment of schizophrenia. Conclusions:ECT is as effective, if not more so, than the antipsychotic drugs in certain clinical settings. It can be rapidly effective in acute episodes. When used alone, antipsychotics have comparable or superior efficacy to ECT alone in the short term. However, ECT possibly confers better long-term outcome. Combination treatment with antipsychotic medications and ECT is superior to either treatment alone, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…14,15 In addition to the expanding evidence base for efficacy and safety, there have been several recent studies helping define whom to consider for ECT. In line with the conclusions from the review by Keuneman et al, 1 it appears that patients who have affective symptoms do not necessarily respond better to ECT, as was once previously thought. In a study of 253 patients, Chanpattana and Sackeim found that presence of affective symptoms did not predict an improved response.…”
Section: Psychiatrysupporting
confidence: 81%
See 2 more Smart Citations
“…14,15 In addition to the expanding evidence base for efficacy and safety, there have been several recent studies helping define whom to consider for ECT. In line with the conclusions from the review by Keuneman et al, 1 it appears that patients who have affective symptoms do not necessarily respond better to ECT, as was once previously thought. In a study of 253 patients, Chanpattana and Sackeim found that presence of affective symptoms did not predict an improved response.…”
Section: Psychiatrysupporting
confidence: 81%
“…Given the earlier finding, 1 that those patients with shorter episode duration of psychosis are more likely to respond and the commonly held view of a need to intervene early in the treatment of psychosis, arguably, as clinicians we should consider ECT as a therapy earlier rather than later in the disease course. In this context, the purpose of this article is to revisit what the recent evidence base now tells us in terms of clinical messages for patients with schizophrenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação às diferenças nas doses médias usadas por homens e mulheres, estas podem ser explicadas pelas características hormonais de cada sexo. As mulheres apresentam maior propensão biológica e psicossocial a terem mais transtornos de humor e de ansiedade, já os homens são mais susceptíveis à esquizofrenia 28,29 . Isso pode explicar por que as mulheres usaram doses maiores de diazepam e os homens clorpromazina.…”
Section: Discussionunclassified